Effects of changing riparian topography on the decline of ecological indicators along the drawdown zones of long rivers in China - Arif, Muhammad; Petrosillo, Irene; Changxiao, Li (Frontiers in Forests and Global Change, 2024)
Riparian topographical features can drive a suite of ecological indicators (EIs) that shape the river ecosystem. The mechanisms that EIs reflect provide several ecosystem services. We know little about the responses of EIs (indicators of plant cover, regeneration, exotics, habitat, erosion, and stressors) to the changing stream-channel width, riparian width, and elevation of the lengthy drawdown zones (upstream, midstream, and downstream) of long rivers. We have discovered that changing topographical characteristics affect riparian buffer areas differently by using a rapid field-based method with 297 transects in inundated regions along the Yangtze River and other 36 linked tributaries in China. Changing stream-channel widths was most effective on downstream EIs and the least effective at midstream. The exotic parameters were the most affected (with a range of −0.36 < r < 0.401) by stream-channel widths, as determined using Pearson correlation (p < 0.05). In contrast, the changing riparian width had the uppermost impact on the upstream EIs and the lowermost impact downstream; riparian width had the most significant impact on habitat parameters (with r ≤ 0.787). The elevation followed the riparian width pattern and was negatively associated with habitat and exotics (r ≤ −0.645 and r ≤ −0.594) and positively correlated with regeneration (r ≤ 0.569). These results reaffirm the imperative need for studies on regionally dependent riparian areas maintained under the same management strategies regardless of their topographical features. Future policies should be formulated to enhance ecosystem service provision, promoting the sustainable use of extensive river ecosystems while considering EIs. Additionally, these future policies should acknowledge drawdown zone factors within the same river network. Furthermore, additional measures are imperative to conserve topographical features and prevent further destruction.